2016
DOI: 10.3386/w22378
|View full text |Cite
|
Sign up to set email alerts
|

Cash for Carbon: A Randomized Controlled Trial of Payments for Ecosystem Services to Reduce Deforestation

Abstract: This paper evaluates a Payments for Ecosystem Services (PES) program in western Uganda that offered forest-owning households cash payments if they conserved their forest. The program was implemented as a randomized trial in 121 villages, 60 of which received the program for two years. The PES program reduced deforestation and forest degradation: Tree cover, measured using high-resolution satellite imagery, declined by 2% to 5% in treatment villages compared to 7% to 10% in control villages during the study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Our study corroborates the findings from Western Uganda by Jayachandran et al . (), who found that PBIP schemes improve the effectiveness of conservation interventions in Uganda. Our findings are also in accordance with Ferraro & Simpson (), Narloch et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our study corroborates the findings from Western Uganda by Jayachandran et al . (), who found that PBIP schemes improve the effectiveness of conservation interventions in Uganda. Our findings are also in accordance with Ferraro & Simpson (), Narloch et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are several other key contextual and design differences between the two studies that makes a direct comparison of the relative efficacy of conservation payment schemes with different degrees of conditionality difficulty. Yet the Jayachandran et al (2017) study has some useful similarities to ours, for example they also focus on assessing short-term impacts on land cover and provide payments that are comparable in magnitude to ours. This allows for a useful comparison of our corresponding results.…”
mentioning
confidence: 73%
“…To our knowledge, this study constitutes one of the first randomized controlled trials (RCT) to analyze the impact of conservation payments in the context of (tropical) deforestation and land use change. 1 Beyond a project by Jayachandran et al (2017) that was conducted concurrently to our study all previous work relies on observational data to assess the impacts of conservation policies on land cover (e.g., see Blackman 2012 for a review). 2 Despite advances in using observational methods to assess conservation policies, important challenges remain in terms of the formulation of a counterfactual scenario, and in overcoming selection bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al (2015) also report on the effects of the REDD+ pilot in Nepal on timber extraction signs observed in the sampled forest plots, finding a negative effect of –0.17 SMD (95% CI [−0.34, −0.01]). In Uganda, Jayachandran et al (, 2017) also report on the effects of the PES experiment on various forest extraction measures. They find a negative effect on cutting of trees in the past year of −0.30 SMD (95% CI [−0.43, −0.18]) and a negative effect of cutting trees for timber products of −0.23 SMD (95% CI [−0.35, −0.10]).…”
Section: Resultsmentioning
confidence: 99%